Istishab Dan Aplikasinya Dalam Sistem Ekonomi Syariah - Adillah Sofiya Ananda; M Difach Hazairin; Syakira Rifdahayani Yoes (Universitas 17 Agustus 1945 Semarang, 2023)
Istishab is a legal principle in the Shariah economic system that plays a crucial role in establishing justice and security in economic transactions. This principle respects the validity of the law in a transaction as long as there is no clear and strong evidence to the contrary. Istishab serves in ensuring legal certainty, protecting the rights of involved parties, preventing doubts and confusion, supporting principles of justice, and minimizing controversies and disputes in Shariah economic transactions. Additionally, it upholds legal continuity and reinforces products and services that adhere to Shariah principles. The research methods employed include literature review, comparative analysis, case studies, surveys, and interviews.